Lack of membrane sex steroid receptors for mediating rapid endocrine responses in molluscan nervous systems - Fodor, István; Matsubara, Shin; Osugi, Tomohiro; Shiraishi, Akira; Kawada, Tsuyoshi; Satake, Honoo; Pirger, Zsolt (Frontiers in Endocrinology, 2024)
Despite the lack of endogenous synthesis and relevant nuclear receptors, several papers have been published over the decades claiming that the physiology of mollusks is affected by natural and synthetic sex steroids. With scant evidence for the existence of functional steroid nuclear receptors in mollusks, some scientists have speculated that the effects of steroids might be mediated via membrane receptors (i.e. via non-genomic/non-classical actions) -a mechanism that has been well-characterized in vertebrates. However, no study has yet investigated the ligand-binding ability of such receptor candidates in mollusks. The aim of the present study was to further trace the evolution of the endocrine system by investigating the presence of functional membrane sex steroid receptors in a mollusk, the great pond snail (Lymnaea stagnalis). We detected sequences homologous to the known vertebrate membrane sex steroid receptors in the Lymnaea transcriptome and genome data: G protein-coupled estrogen receptor-1 (GPER1); membrane progestin receptors (mPRs); G protein-coupled receptor family C group 6 member A (GPRC6A); and Zrt-and Irt-like protein 9 (ZIP9). Sequence analyses, including conserved domain analysis, phylogenetics, and transmembrane domain prediction, indicated that the mPR and ZIP9 candidates appeared to be homologs, while the GPER1 and GPRC6A candidates seemed to be non-orthologous receptors. All candidates transiently transfected into HEK293MSR cells were found to be localized at the plasma membrane, confirming that they function as membrane receptors. However, the signaling assays revealed that none of the candidates interacted with the main vertebrate steroid ligands. Our findings strongly suggest that functional membrane sex steroid receptors which would be homologous to the vertebrate ones are not present in Lymnaea. Although further experiments are required on other molluscan model species as well, we propose that both classical and non-classical sex steroid signaling for endocrine responses are specific to chordates, confirming that molluscan and vertebrate endocrine systems are fundamentally different.